Analisis Petenapatan Harga Jual Pada UMKM Ayam Bakar Taliwang Pak Lalu Karawang - Nelia Wulan Safitri; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine and analyze how to set the selling price of Taliawang Pak Lalu Grilled Chicken. The method used in this study is direct observation of the object under study and interviews to obtain data on data related to the cost of goods produced and the determination of the selling price of MSME production. The data used are primary and secondary data Data Management Techniques and Data Analysis By calculating the entire cost of production raw materials by including factory overhead costs, labor costs, raw material costs, calculation of cost of goods produced and calculation of selling prices. The results of this study are calculated using the cost plus pricing method in table 12 of cost plus pricing costs in the cost plus pricing method using a 30% mark up, which is Rp. 12,000 with a selling price of Rp. 16,000 so that there is a difference, namely where the selling price set by MSMEs Grilled Chicken Taliwang Pak Lalu is currently higher at Rp. 17,000 per portion, if compared with the selling price based on the cost plus pricing method, which is Rp. 16,000 with a profit achievement of 30%, this can cause a price difference of Rp. 1000. Keywords: cost plus production, production cost, selling price